Complete Advanced: Teacher's Book - Brook-Hart G.; Haines Simon (Cambridge Cambridge University Press, 2014)
Complete Advanced provides thorough preparation for the revised 2015 Cambridge English: Advanced (CAE) exam. This Teachers Book contains extensive teaching notes on how to get the most out of the Students Book, with suggestions for warmers and extension activities. There is a full answer key and recording script. The Teachers Resources CD-ROM contains progress tests with two versions of each test to stop students sharing answers. It also provides word lists with definitions along with a range of photocopiable activities and teaching notes. A full practice test is available online for teachers to access.
Keywords: 811.111